Hierarchiczne metody klasyfikacji w analizie danych symbolicznych - Wilk, Justyna (Hierarchical Clustering Methods in Symbolic Data Analysis, 2005)
The article looks at the types and concepts of symbolic data and then attempts to review the available hierarchical clustering methods (traditional and symbolic) to analyze. Symbolic data were defined and contrasted with classical data and the examples were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 376-386